2014
DOI: 10.1371/journal.pone.0113315
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 4q21.23-22.1 Is a Prognostic Marker for Disease Free and Overall Survival in Non-Small Cell Lung Cancer

Abstract: This study was performed to assess the prognostic relevance of genomic aberrations at chromosome 4q in NSCLC patients. We have previously identified copy number changes at 4q12-q32 to be significantly associated with the early hematogenous dissemination of non-small cell lung cancer (NSCLC), and now aim to narrow down potential hot-spots within this 107 Mb spanning region. Using eight microsatellite markers at position 4q12-35, allelic imbalance (AI) analyses were performed on a preliminary study cohort (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Supporting the assumption that HERC5 could be used as a prognostic marker, methylation at cg08750951, using a cut‐off β ‐value of 0.4 (40% methylation) predicts 5 year survival of Stage I ADC patients in a separate independent patient group. Interestingly HERC5 is located within the narrow hot spot region identified in our recent study, which found loss of 4q21.2–22.1 to be an independent poor prognostic factor in NSCLC . These results strongly suggest that HERC5 may be involved in the tumor dissemination of NSCLC and may qualify as a negative prognostic factor.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Supporting the assumption that HERC5 could be used as a prognostic marker, methylation at cg08750951, using a cut‐off β ‐value of 0.4 (40% methylation) predicts 5 year survival of Stage I ADC patients in a separate independent patient group. Interestingly HERC5 is located within the narrow hot spot region identified in our recent study, which found loss of 4q21.2–22.1 to be an independent poor prognostic factor in NSCLC . These results strongly suggest that HERC5 may be involved in the tumor dissemination of NSCLC and may qualify as a negative prognostic factor.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, allelic imbalance analyses and FISH studies identified the core region 4q21.2–22.1, which was significantly associated with worse prognosis. In addition, the same loss could be identified in single DTCs, pinpointing the importance of this region in metastasis …”
mentioning
confidence: 66%
See 2 more Smart Citations
“…This region accounts for ~107 Mbp in length and similar deletions have been associated with either poor prognosis or advanced disease stages in pancreatic, colorectal, non-small cell lung cancer (NSCLC), and HCC tumors [ 42 – 46 ]. Within NSCLC specifically, FISH assays identified the primary region of 4q21.2-22.1 to be associated with poor prognosis [ 44 , 46 , 47 ], and a recent study from this same group showed that hypermethylation of HERC5 promoter (located at 4q22.1), and thus under-expression of the gene correlated with: positive disseminated tumor cells in the bone marrow, brain metastasis, and poor survival in both stage I adenocarcinoma and metastatic lung cancer patients [ 46 ]. Our results presented here in primary tumors of HCC patients are in agreement with these reports, underscoring the prognostic significance of HERC5 under-expression, as we have demonstrated with microarray or RNASeq technologies in primary tumors of three independent cohorts of HCC patients.…”
Section: Discussionmentioning
confidence: 99%